Design and implementation of operating system for modular microgrid - Zhang, Longqi (2017)
Power Park comprised of multiple modular microgrids exhibits advantages including better control flexibility, higher scalability, higher reliability, etc. The Energy Management System (EMS) of the Power Park can be divided into three layers, namely, converter layer, microgrid module layer and power park layer. We designed a two-layer communication network which connects the three control layers and corresponding EMS function blocks like Economic Dispatch (ED) and Unit Commitment (UC). Conventional EMS software can be only deployed on Windows PC with specified costly accessories and licenses which blocked the miniaturization and economization of the modular microgrid. In order to realize system control objectives in different layers, we designed and implemented a cross-platform agent-based microgrid Operating System (OS). Its components including Agent, Active Application Program Interface (API), Passive API and Graph User Interface (GUI) are designed and implemented to coordinate various converters based on the communication network. We implemented the real-time controller as the main component of the microgrid OS for executing functions like secondary voltage/frequency regulation, contingency analysis, etc. to enhance control accuracy within the microgrid.